Behavioral and Living Environmental Factors Associated with Dengue Haemorrhagic Fever Prevalence in Air Dingin Public Health Center, Padang City - ., Masrizal; Wiratni, I; Putra, O (KnE Life Sciences, 2019)
Dengue Hemorrhagic Fever (DHF) is a major public health problem in Indonesia. An Incidence Rate (IR) of 361/100.000 population was accounted at Air Dingin. The purpose of this study was to know the relationship between living environment and 3M Plus behavior with DHF prevalence in Air Dingin. A case-control study with simple random sampling was conducted at Air Dingin Public Health Center from December to June 2016. The samples were divided into two groups of case and control groups of 39 while controlling the age and domicile. The obtained data was then analyzed using univariate, bivariate, and multivariate analysis. Bivariate analysis results showed : the house temperature p-value = 0.065 ; humidity houses p-value = 0.687 ; light p-value = 0.002; density residential home p-value= 0.359 ; drain water reservoirs p-value = 0.359 ; close water reservoirs p-value = 0.179 ; buy thrift p-value= 0.002 ; insect screen use p-value = 0.179 ; and hanging clothes behavior p-value = 0.014. Multivariate analysis result showed that the dominant factor was the lighting (p-value=0.029 OR=3.34). Three variables had significant relationship with DHF prevalence : lighting, waste products burying/disposing behavior and hanging clothes behavior. Keywords: DBD; environment home; practice 3M Plus